Fintech peer to peer lending as a financing alternative for the development MSMEs in Indonesia - Fry Anditya Rahayu Putri Rusadi; Kornelius Benuf (Legality : Jurnal Ilmiah Hukum, 2020)
The main problem faced by Micro, Small and Medium Enterprises (MSMEs) actors is limited access to finance. The presence of Fintech Peer to Peer Lending companies in Indonesia is the answer to the limited access to finance faced by MSME entrepreneurs. However, the presence of Fintech Peer to Peer Lending for MSMEs in Indonesia can cause legal problems. This study aims to find a juridical basis for the relation between Fintech Peer to Peer Lending organizers and MSME entrepreneurs and to find constitutional protection for Fintech Peer to Peer Lending organizers and MSME entrepreneurs. The method used is juridical empirical, using primary data in the form of primary and secondary legal materials. The study outcomes concluded that the weak legal protection for the lenders (borrowers), which in this case is MSMEs, is due to the insufficiency of strict legitimate rules in managing the Fintech Peer to Peer Lending business. So that the implementation of the Peer to Peer Lending Fintech business needs to be regulated under the Law so that it can be charged with criminal sanctions.